READY4CAREER MODEL FOR GEN Z EMPLOYABILITY AND CAREER READINESS - Ibrahim, Siti Balkis Mohamed; Alias, Nur Salimah; Ali, Wan Nor Ashiqin Wan; Marzuki, Izati Nabila; Abdullah, Farah Zahidah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
Rapid changes of labour market were driven by digitalisation, post-pandemic disruptions, and evolving generational characteristics have intensified challenges surrounding graduate employability, particularly among Generation Z. In the Malaysian context, graduates increasingly encounter psychological vulnerability, unclear professional identity, limited career literacy, and difficulties in workplace transition, which collectively contribute to persistent underemployment and early career instability. These realities underscore the necessity for a holistic and development-oriented career readiness framework that extends beyond conventional technical and skill-based models. This study proposes the Ready4Career Model, a seven-dimensional developmental framework comprising Discovery (Self-Discovery), Identity (Professional Identity), Affect (Emotional Stability), Mastery (Resume and CV Mastery), Occupational Literacy (Career Literacy), Navigational Readiness (Interview and Workplace Transition), and Development (Continuous Growth). Grounded in Career Construction Theory, the model conceptualises career development as a dynamic and continuous process shaped by self-regulation, identity construction, adaptability, and lifelong learning. Employing a qualitative conceptual methodology through structured narrative synthesis of contemporary international and Malaysian literature published between 2020 and 2025, this study systematically integrates psychological, educational, and employability perspectives into a coherent framework. The findings highlight the model’s theoretical coherence, contextual relevance, and practical applicability in enhancing emotional resilience, professional identity clarity, career adaptability, and graduate readiness. Overall, the Ready4Career Model provides an evergreen and adaptable framework to support higher education institutions, policymakers, and career practitioners in strengthening sustainable graduate employability within an increasingly complex employment scope.